Mycetoma in an HIV-infected patient - Castro, Luiz G. M.; Valente, Neusa Y. S.; Germano, José Antônio M.; Vaccari, Elisabeth M. Heins; Lacaz, Carlos da Silva (Revista do Hospital das Clínicas, 1999)
Although oportunistic fungal infections occur commonly in immunocompromised hosts, mycetoma has never been reported in association with HIV infection. The authors present a case that to their knowledge is the first reported case of mycetoma associated with HIV infection. Diagnosis was confirmed by direct examination of grains and histologic examination. Precise identification of the agent, an actinomycete, was not possible. The unusual site of infection may probably be related to the use of contaminated needless and sirynges for HIV drug injection.